The Impact of Intrusive Advising on Student Retention and Success in STEM Education: An Empirical Study - Haneen, Muhammad Gul (Journal of Educational Research and Policies, 2025)
Intrusive advising is a type of student advising characterized as a highly interactive and proactive student-centered process. Intrusive advising, like traditional advising frameworks such as developmental and prescriptive advising, is essential for identifying and designing remediation approaches to ensure student success and retention. Intrusive advising involves deliberately administrating Tinto’s academic and social integration objectives. Data indicates that intrusive advising is an effective strategy for improving student undergraduate success and academic retention rates. Intrusive advising may also advance research training and career development goals. Most of the data on this topic focuses on the first two years of college. More data is needed to explore the impact of intrusive advising on the last two years of college to understand better how intrusive advising mediates persistence, graduation, and entry into graduate school, professional school, or the job market. Further, more targeted information is needed to explore how intrusive advising improves student progression and degree completion for science, technology, engineering, and math (STEM) majors. The current article has significant implications for student advising policy and practice. Intrusive advising methods may be essential for minority-serving institutions with retention rates well below the national average.